2007
DOI: 10.1177/1352458506071216
|View full text |Cite
|
Sign up to set email alerts
|

Familial clustering of multiple sclerosis in a Dutch genetic isolate

Abstract: Multiple sclerosis (MS) is a complex disease with a substantial, yet poorly identified, genetic influence. We estimated the pattern of familial aggregation of MS in a recent genetically isolated population in The Netherlands. Forty-eight MS patients were identified. Their relationship was evaluated by tracing extended pedigrees, making use of municipal and church records. Of the 48 MS patients, 24 could be linked to a common ancestor in 14 generations. However, multiple relationships exist between patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…Familial aggregation of MS has been recognized earlier [3,7,11]. Relatively recently, a study from the Netherlands suggested familial clustering in a genetically isolated population, wherein 24 of 48 MS patients could be linked to a common ancestor in 14 generations as a result of a high level of inbreeding [12]. Consanguineous marriages are widely practiced in Kuwait, which results in increased homozygosity [13].…”
Section: Discussionmentioning
confidence: 99%
“…Familial aggregation of MS has been recognized earlier [3,7,11]. Relatively recently, a study from the Netherlands suggested familial clustering in a genetically isolated population, wherein 24 of 48 MS patients could be linked to a common ancestor in 14 generations as a result of a high level of inbreeding [12]. Consanguineous marriages are widely practiced in Kuwait, which results in increased homozygosity [13].…”
Section: Discussionmentioning
confidence: 99%
“…2 Originally, 48 MS patients (13 male, 35 female) were included. Later on, another female MS patient was identified and included.…”
Section: Participants From the Dutch Genetically Isolated Populationmentioning
confidence: 99%
“…Although most were originally diagnosed as sporadic MS patients, a total of 25 (51%) could be linked to an extended pedigree. 2 Three of the 49 MS patients were excluded from analysis because they were sisters of one MS patient. Clinical characteristics from the 46 MS patients who were included for analysis are described in Table 3a.…”
Section: Participants From the Dutch Genetically Isolated Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in a Dutch isolate found MS patients to be significantly more related to each other than the control group, and more often inbred (82% compared with 36%). 21 Sadovnick et al 22 found the sibling recurrence rate of MS to be almost four times as high among offspring of consanguineous parents than among those of unrelated parents (8.0% compared with 2.3%). Evidence for the importance of a founder effect in explaining the high prevalence of MS in the Southern Ostrobothnian region of western Finland has been found, which is also consistent with a possible role of recessive effects in MS aetiology.…”
Section: Introductionmentioning
confidence: 99%